Evaluating the use of a Net-Metering mechanism in microgrids to reduce power generation costs with a swarm-intelligent algorithm. (1st March 2023) - Marcelino, C.G.; Leite, G.M.C.; Wanner, E.F.; Jiménez-Fernández, S.; Salcedo-Sanz, S.
Abstract: The micro-generation of electricity arises as a clean and efficient alternative to provide electrical power. However, the unpredictability of wind and solar radiation poses a challenge to attend load demand, while maintaining a stable operation of the microgrids (MGs). This paper proposes the modeling and optimization, using a swarm-intelligent algorithm, of a hybrid MG system (HMGS) with a Net-Metering compensation policy. Using real industrial and residential data from a Spanish region, a HMGS with a generic ESS is used to analyze the influence of four different Net-Metering compensation levels regarding costs, percentage of renewable energy sources (RESs), and LOLP. Furthermore, the performance of two ESSs, Lithium Titanate Spinel ( Li 4 Ti 5 O 12 (LTO)) and Vanadium redox flow batteries (VRFB), is assessed in terms of the final $/kWh costs provided by the MG. The results obtained indicate that the Net-Metering policy reduces the surplus from over 14% to less than 0.5% and increases RESs participation in the MG by more than 10%. Results also show that, in a yearly projection, a MG using a VRFB system with a 25% compensation policy can yield more than 100000$ dollars of savings, when compared to a MG using a LTO system without Net-Metering. Highlights: A mathematical modeling to electric dispatch by use net-metering police is done. The effectiveness of the Net-Metering approach in a Spanish scenario is carried out. An in-depth performance assessment of two distinct storage systems are evaluated. A economic projection has been done resulting in a profit with the approach proposed.